Current management of xerostomia in head and neck cancer patients - Nathan, C-AO; Asarkar, AA; Entezami, P; Corry, J; Strojan, P; Poorten, VV; Makitie, A; Eisbruch, A; Robbins, KT; Smee, R; St. John, M; Chiesa-Estomba, C; et al. (Elsevier, 2023)
Radiotherapy (RT) continues to play a key role in the management of head and neck cancer (HNC). Xerostomia remains a principal detriment to the quality of life (QoL) for 80 % of surviving patients receiving head and neck radiation. Radiation-induced injury to the salivary glands is dose-dependent, and thus efforts have been focused on decreasing radiation to the salivary glands. Decreased saliva production reduces both short-term and long-term quality of life in head and neck survivors by impacting on taste and contributing to dysphagia. Several radioprotective agents to the salivary gland have been investigated. Although not widely practiced, surgical transfer of the submandibular gland prior to RT is the mainstay of surgical options in preventing xerostomia. This review focuses on the strategies to improve xerostomia following radiation therapy in head and neck cancers.